Studi Empiris Tentang Brand Trust Bank XX Di Jakarta dalam Perspektif Komunikasi - Ayu Yulianti Putri; La Mani; Theresia Febrian; Yohanes Lukman (J-MAS (Jurnal Manajemen dan Sains), 2023)
This research was conducted to determine Brand Trust through customer satisfaction in influencing customer loyalty at Bank XX Jakarta. The type of research used in this research is quantitative research with a descriptive approach. The analysis technique used is quantitative verification analysis, through structured interviews using questionnaires. The population in this study is Bank XX customers in South Jakarta whose number is unknown and can be said to be in the infinite category. The type of sample used in this study is Lemeshow. Data analysis in this study used the Partial Least Square (PLS) approach. The results of this study are all variables have a positive and significant effect. In this study, there are eight related variables, namely X1 (interest rate), X2 (customer service communication strategy), X3 (customer experience), X4 (service quality), X5 (digital banking) ,X6 (customer satisfaction), X7 (brand trust), X8 (loyalty) have a positive and significant effect. The conclusion of this study is that all variables have a positive and significant effect so that XX Bank always maintains and improves customer satisfaction and loyalty by maximizing service quality.